“ALL-ON-6”, ADVANTAGES AND DISADVANTAGES OF THIS MODERN DENTAL RESTORATION SOLUTION - Oleg Solomon; Viorica Chetrus; Anamaria Zaharescu; Razvan Leata; Mariana Ilie; Antoanela Magdalena Covaci; Kamel Earar (Romanian Journal of Oral Rehabilitation)
The All-on-6 technique is a modern and effective solution for complete tooth restoration, using six dental implants to support a fixed denture. This method provides excellent long-term results, with significant benefits in terms of durability, stability, and functionality of the implants. Titanium implants, once integrated into the bone through the osseointegration process, can last for decades, and the prosthesis attached to them provides patients with an experience similar to that of natural teeth. One of the major advantages of the All-on-6 technique is the prevention of bone resorption, a common problem in patients who have lost teeth. The implants stimulate the jawbone, maintaining volume and preventing facial changes associated with bone loss. In the long term, the success of this treatment depends on rigorous oral hygiene and regular visits to the dentist for denture maintenance and monitoring of the condition of the implants. Although the risks of complications such as peri-implantitis or osseointegration failure exist, they are rare and can be prevented with proper care. In conclusion, All-on-6 offers a durable, aesthetic and functional solution for patients with severe tooth loss.